PELATIHAN KEWIRAUSAHAAN BAGI KELOMPOK TANI DAN NELAYAN DI PESISIR PANTAI TUMPAAN MELALUI PEMANFAATAN LIMBAH AIR KELAPA - Ramon Arthur Ferry Tumiwa; Freddy Semuel Kawatu (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
Kumu village located on the coast of Tumpaan is part of Tombariri subdistrict of Minahasa regency has a large coconut plantation. Limited knowledge of farmers to the problem of processing agricultural products into a series of problems that are never solved. Farmers and farmers in Kumu village do not understand about entrepreneurship and do not yet have innovation in processing agricultural products that have added value in improving the family economy. They have not utilized coconut water waste in the manufacture of copra. The solution that has been done is to answer the above problems through community service activities, namely,providing Entrepreneurship Training for Farmers and Fishermen Groups including good and correct coconut water waste,as well as knowledge and skills to handle post-harvest.